Interações do sistema circadiano com a atividade física e a temperatura ambiente - Frederico Sander Mansur Machado (2017)
The internal biological clock can be synchronized by different entraining agents or zeitgebers. Regular physical activity and temperature cycles would be secondary stimuli for the synchronization of the circadian system to daily light/dark cycles. Therefore, the present study investigated both the effect of physical exercise on the circadian system and the influence of daylight hours on the physiological adjustments induced by cold exposure in Wistar rats. In the first experiment, the effect of a single physical exercise session (groups: rest, submaximal exercise at 40 and 70% of the average maximum velocity verified for the evaluated population, exercise test until fatigue) was investigated in different components of the circadian system: the expression of clock genes in skeletal msucle and adrenal (rtPCR); corticosterone secretion (ELISA); the oscillations of body temperature and locomotor activity (telemetry). In the second experiment the effect of physical training on several levels of the circadian system under resting conditions was evaluated: the cycle of the expression of the clock genes in skeletal muscle (rtPCR); the corticosterone cycle (ELISA), the oscillations of body temperature and locomotor activity (telemetry); cycles of serotonergic and dopaminergic activity in the central nervous system (HPLC). After 8 weeks of training, the animals were euthanized at different times of the day to harvest brain, gastrocnemius muscle and blood. In the third experiment the effect of day-time on the physiological adjustments (telemetry and indirect calorimetry) and the peripheral clock (rtPCR) in response to acute cold exposure were studied. The animals were submitted to conditions of constant ambient temperature (23 ° C) or cold environment (4 ° C) at six times of the day for 3 hours. Immediately after the animals were euthanized to harvest brown adipose tissue and soleus muscle. When performed during the resting phase of the light / dark cycle, physical exercise temporarily altered the circadian thermal balance by elevating body temperature independently of sustained increases in locomotor activity. This transitory imbalance in the balance between body temperature and locomotor activity was accompanied by an elevated-dependent workload on corticosterone levels immediately after exercise. Surprisingly, exposure of the animals to the treadmill without exercise induced an elevation in the transcription of PER1 in gastrocnemius, attenuated in a inverse proportion to the workload performed during the exercise. In turn, when performed with a regular schedule and for 8 weeks, physical exercise promoted adjustments in the daily heat balance by increasing the levels of locomotor activity during the active phase, especially in the last hours of this phase of the day. Centrally, such changes were accompanied by changes in serotonergic and dopaminergic activity in the preoptic area and serotonergic activity in the paraventricular nucleus of the hypothalamus. Peripherally, despite the similarity in the circulating corticosterone cycle, the training induced an increase in the transcription of PER1 in the gastrocnemius, especially during the transition from the dark phase to the light phase, indicating an adaptation of the peripheral clock. Finally, an attenuation of substrate shift evoked by cold exposure during the resting phase was observed. Such alteration was accompanied by mild hyperthermia associated with increased metabolic rate. In addition, the time of day influenced the intensity of the expression of several molecular components of the peripheral clock, such as CLOCK, PER1, CRY1, CRY2 and REV-ERBα in different ways for the soelus muscle and the brown adipose tissue, suggesting the participation of the peripheral circadian system in modulating the response to cold. Thus, the present study demonstrated that physical exercise can influence the circadian system by peripherally modulating clock or clock gene activity and also by promoting adjustments in basal monoaminergic activity cycles in areas directly involved in the control of body temperature and thermal balance. In addition, it was characterized not only the importance of the time of day for the intensity of the metabolic adjustments to the cold environment, but also the likely participation of the peripheral clock in the modulation of these responses.